BAHASA INGGRIS - Hilma Safitri; Siti Husnia (Program Studi Pendididikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2026)
The objectives of this study were to find out the common types of simple past errors found in recount texts written by the ninth-grade students of SMPN 03 Muncang Lebak Banten and some causes. Mixed method was employed. 15 ninth-grade students were enrolled in this study. The research instruments were questionnaires, interviews, and some exercises. Some data analysis were conducted by calculating some data quantitative. Meanwhile some data qualitative were analyzed by checking and identifying the categories of errors purposed by Dulay et., in 1982. The results revealed that misinformation type of error was the most common error taking place which was 51(67,11%). Meanwhile, the addition type of error proved to be the least common type of error made by the students (1) 1,32%. The rest are omission (21) 27,63 % and misordering (3) 3,39% respectively. Meanwhile the causes of the students’ errors in writing consist of (1) Carelessness, such as lack of attention and too confidence, (2) First language interference in which it took place in terms of grammar and structure dereference, (3) Translation that is the problem lies on to translate word by word regarding Indonesian structure.